The Influence of Loan to Deposit Ratio (LDR) and Capital Adequacy Ratio (CAR) on Profit Growth at PT. Bank Central Asia, Tbk for the Period 2014-2023 - Saparudin, Aprul; Astuti, Widia (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to determine how the loan-to-deposit ratio (LDR) and capital adequacy ratio (CAR) impact the profit growth of PT. Bank Central Asia (TBK) from 2014 to 2023. Parametric methods, or inferential statistics, are used to determine how variables interact with each other. Statistical Package for the Social Sciences, or SPSS, was used to conduct this research. The research results indicate that the profit growth of PT. Bank Central Asia, Tbk was not influenced by the Loan to Deposit Ratio (LDR) from 2014 to 2023. The calculated t-value is greater than the t-table value, with (-0.218) being greater than 2.365, and the significance value of 0.833 being greater than 0.05. The F-test results indicate that the loan-to-deposit ratio (LDR) and the capital adequacy ratio (CAR) did not impact the profit growth of PT. Bank Central Asia, Tbk from 2014 to 2023. With a calculated t-value < t-table or 0.072 < 2.365, the significance value of 0.944 is greater than the test level of 0.05